Domestic violence in rural currently married women: effects on utilization of reproductive and maternal health services - Gupta, Rajiv Kumar; Langer, Bhavna; Singh, Parveen; Kumari, Rashmi; Akhter, Najma; Gupta, Riya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Domestic violence remains a public health concern in India due to its high prevalence and adverse effects on pregnancy outcomes. Domestic violence in low and middle income countries has emerged as a priority among researchers and policy makers who are primarily concerned with women s health and empowerment. The study aimed to assess the relationship between domestic violence and women’s use of reproductive and maternal health services. Methods: The present study was conducted among currently married rural women in reproductive age group (15-49 Years). Four villages in Kot Balwal Block were selected randomly and all the currently married women who were willing to give informed verbal consent were administered the questionnaire. The questionnaire was pilot tested by the authors. Data was analysed using proportion sand chi square test was used as a test of significance. Results: Prevalence of domestic violence was reported to be 49.12%. Regarding empowerment, the results revealed that while 65.3% of the respondents were able to decide on their health, only 20.7% had say in household purchases. Attitude towards wife beating was strongly negative as 95.7% rejected wife beating. Levels of education, exposure to media, intake of alcohol by partners and spousal age difference were statistically significant (p<0.05) in relation to use of reproductive and maternal health services. Conclusions: The study has revealed that women’s empowerment has a positive impact on use of reproductive and maternal health services. Multi-sector collaboration in initiating programs and interventions to improve women’s empowerment, increase educational attainment and reduction of gender based violence should be a priority for the health planners.